2021
DOI: 10.1101/2021.11.03.467114
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synthesis and antimicrobial evaluation of new cephalosporin derivatives containing cyclic disulfide moieties

Abstract: Due to a steady increase of microbial resistance, there is a need to increase the effectiveness of antibiotic performance by involving additional mechanisms of their penetration or retention for their better action. Cephalosporins are a successful group of antibiotics to combat pathogenic microorganisms, including drug-resistant strains. In this study, we investigated the effect of newly synthesized cephalosporin derivatives with cyclic disulfide modifications against several Gram-positive and Gram-negative st… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…[28][29][30]34 For bacteria, such reports are scant and in fact antibiotics acting in the cytoplasm were inactivated via their conversion to disulfide-containing derivatives, possibly suggesting conjugation to the bacterial cell surface and thereby arrested drug cell entry. 31 In recent studies, Shchelik and Gademann 51,52 observed that the disulfide containing derivatives of vancomycin and cephalosporin were superior to the parent antibiotic molecules, although no mechanism for the involvement of the disulfide functionality was provided to explain the enhanced drug efficacy of the newly synthesized compounds. In our hands, attempts to block the bacterial cell surface thiols with maleimide-based sulfhydryl poisons 30 were met with limited success (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30]34 For bacteria, such reports are scant and in fact antibiotics acting in the cytoplasm were inactivated via their conversion to disulfide-containing derivatives, possibly suggesting conjugation to the bacterial cell surface and thereby arrested drug cell entry. 31 In recent studies, Shchelik and Gademann 51,52 observed that the disulfide containing derivatives of vancomycin and cephalosporin were superior to the parent antibiotic molecules, although no mechanism for the involvement of the disulfide functionality was provided to explain the enhanced drug efficacy of the newly synthesized compounds. In our hands, attempts to block the bacterial cell surface thiols with maleimide-based sulfhydryl poisons 30 were met with limited success (data not shown).…”
Section: Discussionmentioning
confidence: 99%